Antitumor activity and ability to prevent acrylamide formation in fried foods of asparaginase from soybean root nodules. Issue 3 (7th January 2019) - Liu, Chun; Luo, Lijuan; Lin, Qinlu
Abstract: A novel asparaginase (designated srnASNase) has been purified from soybean root nodules and identified by MALDI‐TOF/TOF‐MS. And the enzymatic properties, antitumor activity and the ability to prevent acrylamide formation in fried foods of srnASNase were evaluated. SrnASNase had high specific activity (531.37 U/mg) toward L‐asparagine under optimum conditions (pH 8.0 and 40°C), no activity toward L‐glutamine and D‐glutamine, but trace activity toward D‐asparagine. It was stable in the pH range of 7.0–9.0 and up to 40°C. The Km and V max of srnASNase were 0.36 mM and 51.64 mM/min, respectively. Further, in vitro anti‐proliferative activity on human cancer cells assay showed that srnASNase was superior to commercial asparaginase in solution by controlling the tumor cell growth with time. In addition, srnASNase showed more effective acrylamide mitigation than commercial asparaginase in fried foods. These results indicate that srnASNase is a potential candidate for applications in the food processing and pharmaceutical industry. Practical applications: L‐asparaginase (L‐asparagine amidohydrolase; EC 3.5.1.1) is an enzyme that catalyzes the hydrolysis of the amide group of the side‐chain of L‐asparagine into aspartic acid and ammonia. It has long been used as a primary component in the treatment of acute lymphoblastic leukemia (All) and other related blood cancers. Apart from its clinical usage, L‐asparaginase has attracted more attention in the food processing industries as a promising acrylamide‐mitigating agent in recent years. This research revealed that soybean root nodules might be good sources of novel asparaginase. Abstract : A novel asparaginase (srnASNase) has been purified and characterized from soybean root nodules. SrnASNase had good enzymatic properties. Further, srnASNase was superior to commercial asparaginase in solution by controlling the tumor cell growth with time. In addition, srnASNase showed more effective acrylamide mitigation than commercial asparaginase in fried foods. These results indicate that srnASNase is a potential candidate for applications in the food processing and pharmaceutical industry.